1999
DOI: 10.1089/cbr.1999.14.451
|View full text |Cite
|
Sign up to set email alerts
|

Combined Modality Therapy of A431 Human Epidermoid Cancer Using Anti-EGFr Antibody C225 and Radiation

Abstract: These data demonstrate an interaction between C225 and RT. C225-mediated apoptosis and inhibition of EGFr phosphorylation may be critical in the interaction. Studies to define the precise influence of combined modality treatment on the EGFr signal transduction cascade need to be pursued. The combination of growth factor receptor antibodies and RT has potential application in clinical oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(65 citation statements)
references
References 2 publications
2
63
0
Order By: Relevance
“…EGFR is stimulated by a number of autocrine growth factors, including EGF and TGFa. Recently, it has been shown that ionising radiation stimulates EGFR activation and cellular proliferation (Schmidt-Ullrich et al, 1997; Dent et al, 1999;Reardon et al, 1999;Todd et al, 1999) and that anti-EGFR antibody approaches can improve tumour radiation response (Saleh et al, 1999;Bianco et al, 2000;Milas et al, 2000). In the present study, we evaluated the potential influence of ZD1839 on the radiation response of the human colorectal carcinoma cell line LoVo which has moderate levels of EGFR expression (33 000 receptors per cell), and is therefore likely to be representative of most epithelial tumour cell lines (Caraglia et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is stimulated by a number of autocrine growth factors, including EGF and TGFa. Recently, it has been shown that ionising radiation stimulates EGFR activation and cellular proliferation (Schmidt-Ullrich et al, 1997; Dent et al, 1999;Reardon et al, 1999;Todd et al, 1999) and that anti-EGFR antibody approaches can improve tumour radiation response (Saleh et al, 1999;Bianco et al, 2000;Milas et al, 2000). In the present study, we evaluated the potential influence of ZD1839 on the radiation response of the human colorectal carcinoma cell line LoVo which has moderate levels of EGFR expression (33 000 receptors per cell), and is therefore likely to be representative of most epithelial tumour cell lines (Caraglia et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous experimental data both in vitro and in vivo showing that EGFR targeting is able to augment the antitumour activity of several anticancer agents including doxorubicin, cisplatin, 5-fluorouracil (5FU), gemcitabine, paclitaxel and topotecan Fan et al, 1993;Ciardiello et al, 1999;Bruns et al, 2000;Inoue et al, 2000;Overholser et al, 2000). Similar enhancement of activity has also been observed in studies combining EGFR-targeting agents, particularly the monoclonal antibody IMC C225 (cetuximab), with ionizing radiation (Huang et al, 1999;Saleh et al, 1999;Bianco et al, 2000;Bonner et al, 2000;Milas et al, 2000). Other investigators (Williams et al, 2002) and this laboratory (Magné et al, 2002a) recently showed supra-additive effects between irradiation and ZD1839, confirming the radiosensitisation conferred by an EGFRtargeting agent.…”
mentioning
confidence: 81%
“…These preclinical indications suggest a role for cetuximab in irinotecan-refractory CRC patients (Prewett et al, 2002). Several preclinical studies have also shown an enhancement of tumor response to radiotherapy by combined treatment with cetuximab in human epidermoid, head and neck, and colon cancer xenografts (Huang et al, 1999;Saleh et al, 1999;Bianco et al, 2000;Huang and Harari, 2000;Milas et al, 2000). Among the potential mechanisms that contribute to the increased radiation sensitivity by treatment with cetuximab, it has been suggested an accumulation of cancer cells in the more radiosensitive cell-cycle phases (G 1 , G 2 -M), a blockade of radiation-induced DNA repair mechanisms, a reduction of VEGF production by cancer cells with inhibition of tumor angiogenesis (Huang and Harari, 2000).…”
Section: Molecular Properties and Clinical Pharmacologymentioning
confidence: 99%